WHEN BAOBAB FLOWERS AND RAINMAKERS DEFINE THE SEASON: FARMERS’ PERCEPTIONS AND ADAPTATION STRATEGIES TO CLIMATE CHANGE IN WEST AFRICA - Zoundji, Gérard; Vodouhê, D. Simplice; Lie, Rico; Witteveen, Loes (My University, 2017)
Climate change is affecting the livelihoods of rural African populations. In fact, farmers, whose livelihoods depend on agriculture, are likely to bear the brunt of climate change impacts. The extent to which these impacts are felt depends in large part on the extent of adaptation in response to climate change. The aim of this paper is to assess Beninese farmers‟ perceptions on climate and adaptation strategies for information and knowledge that may guide decision making and draw the attention on the need to integrate local knowledge in climate adaptation. Focus group discussions and semi-structured interviews were organized with 51 farmers representing diverse farming experiences and farmland positions. In order to make the link between farmers‟ perception on the seasons prediction regarding to plant observation, we identified and observed phenology phases of five Baobab and five cashew plants based on their geographical distribution in the study area. Collected data were analyzed by using the agricultural adaptation and perception model and the dynamic system of knowledge, perception and adaptation. The study shows that farmers have different perceptions of climate change, but at the same time are almost unanimous about the changing of rainfall frequency, which is described as “rain seasons start late and end early”. The study revealed that the Baobab plants flowering phase seems to coincide with the rainy season and confirmed farmers‟ knowledge about good rainy season detecting. The article further lays out that farmers have developed a range of adaptation strategies, which are situated within the three distinguished spaces; the space of agricultural practices, the space of livelihood diversification, and the space of local culture and learning. The study suggests that understanding farmer‟s perceptions and practices and using them as a starting point for adaptation to climate change could help policy makers to formulate sustainable adaptation strategies.
Keywords: adaptation strategies; climate change; farmers‟ perception; rainfall prediction